O discurso de apresentação da gramática: a emergência do sujeito contraditório - Curry, Scheila Patrícia de Borba (2009)
Our Post-Graduation study in Languages aims to investigate how the position subject speaker is built, how it is established and how it works in the discourse of Presentation in grammar. Therefore, we based our study on French Discourse Analysis in which the subject is constituted by a discursive heterogeneity, by an ideological interpellation which moves it from a subject category to different positions of subject of saying and of discourse. Among the positions subject identified there are the positions of: scientist, teacher/professor and grammarian as well as we identified specific functionings of silence (subject speaker position) and of dilution (subject politician subject and producer of Brazilian Grammar Rules - BGR). In fact, the analysis show that the position subject speaker is silenced by the unity brought by the rightness of the norm in his/her speech the same way the positions subject politician and producer of BGR dissolves itself in all the others it is a presence but it does not mark itself linguistically nor discursively. In this study, we delimited as our corpus the sections No limiar and Profissão de fé from the Gramática Normativa da Língua Portuguesa, by Carlos Henrique de Rocha Lima, published in 1991. In our corpus we looked at the functioning of subject positions as well as at which relationships they maintain with each other. From the relationship of the position subject with the linguistic materiality on which it is based, its relation with the language, the history and the symbolic occurs, what guides the relations of signification, affiliating the subject to this and not to that sense (Orlandi, 2003). From this, we look for an understanding on how this space, which slips from a position to another, is discursively built, because this is the space where grammar and the subject who builds grammar enunciate.